A molecular link between autophagy and circadian rhythm in plants. Issue 5 (29th April 2022) - Chen, Weijun; Hu, Zhaotun; Yu, MengTing; Zhu, Sirui; Xing, Junjie; Song, Limei; Pu, Wenxuan; Yu, Feng
Abstract: Extremely high or low autophagy levels disrupt plant survival under nutrient starvation. Recently, autophagy has been reported to display rhythms in animals. However, the mechanism of circadian regulation of autophagy is still unclear. Here, we observed that autophagy has a robust rhythm and that various autophagy‐related genes ( ATGs ) are rhythmically expressed in Arabidopsis . Chromatin immunoprecipitation (ChIP) and dual‐luciferase (LUC) analyses showed that the core oscillator gene TIMING OF CAB EXPRESSION 1 ( TOC1 ) directly binds to the promoters of ATG ( ATG1a, ATG2, and ATG8d ) and negatively regulates autophagy activities under nutritional stress. Furthermore, autophagy defects might affect endogenous rhythms by reducing the rhythm amplitude of TOC1 and shortening the rhythm period of CIRCADIAN CLOCK‐ASSOCIATED 1 ( CCA1 ). Autophagy is essential for the circadian clock pattern in seedling development and plant sensitivity to nutritional deficiencies. Taken together, our studies reveal a plant strategy in which the TOC1‐ ATG axis involved in autophagy‐rhythm crosstalk to fine‐tune the intensity of autophagy. Abstract : The core circadian clock protein TIMING OF CAB EXPRESSION 1 directly regulates autophagy‐related genes, revealing that the circadian clock regulates the balance of cellular energy metabolism through autophagy and ultimately determines the fate of cells.